QUALITY OF LIFE OF FAMILY CAREGIVERS OF CHILDREN WITH LEUKEMIA: A DESCRIPTIVE QUANTITATIVE STUDY - Ikeu Nurhidayah; Sri Hendrawati; Dewi Pratiwi Hasriyadhi (Belitung Raya Foundation, Indonesia, 2020)
Background: Treatment of children with cancer can affect daily lives of family caregivers. This can disrupt roles in social life, limit daily activities, disrupt health and physical and emotional balance as well as causing economic problems and creating poor quality of life. Objective: To describe the quality of life of family caregivers of children with leukemia based on characteristics of parents and children. Methods: This was a descriptive quantitative study. The population was all parents as the primary caregivers who had children aged 0-15 years diagnosed with leukemia in pediatric wards of Provincial General Hospital of Dr. Hasan Sadikin Bandung, Indonesia. Thirty-four respondents participated in this study selected using a total sampling. The quality of life of family caregivers was measured using the quality of life family version standard questionnaire, and the children's severity of leukemia was identified by the severity of illness scale standard questionnaire. Data were analyzed using frequency distribution, mean, and standard deviation. Results: The study results showed that family caregivers had poor quality of life (58.8%), with the worst sub-dimension including physical and psychological health conditions (55.9%), followed by social conditions (52.9%), and spiritual health conditions (50.0%). The majority of family caregivers who had the poorer quality of life were at the older age, male, having a primary education level, caring for their children for less than 12 months with severe leukemia, and having an average monthly income of fewer than 1.5 million rupiahs. Conclusion: Poor quality of life was identified among family caregivers of children with leukemia. Therefore, it is suggested for nurses to provide nursing care holistically not only for the children but also the families to increase their quality of life.